Cell-permeable peptide nucleic acid antisense oligonucleotide platform targeting human betacoronaviruses - Park, Soree; Kim, Seong Ho; Dezhbord, Mehrangiz; Lee, Eun-Hwi; Jeon, Yeasel; Jung, Daram; Gu, Se Hun; Yu, Chiho; Lee, Seung Ho; Kim, Sung Chun; Kim, Kyun-Hwan (Frontiers in Microbiology, 2023)
Antisense oligonucleotides (ASOs) with therapeutic potential have recently been reported to target the SARS-CoV-2 genome. Peptide nucleic acids (PNAs)-based ASOs have been regarded as promising drug candidates, but intracellular delivery has been a significant obstacle. Here, we present novel modified PNAs, termed OPNAs, with excellent cell permeability that disrupt the RNA genome of SARS-CoV-2 and HCoV-OC43 by introducing cationic lipid moiety onto the nucleobase of PNA oligomer backbone.HCT-8 cells and Caco-2 cells were treated with 1 μM antisense OPNAs at the time of viral challenge and the Viral RNA levels were measure by RT-qPCR three days post infection. NSP 14 targeting OPNA 5, reduced the viral titer to a half and OPNA 530, 531 and 533 lowered viral gene expression levels to less than 50% of control by targeting the 5' UTR region. Several modifications (oligo size and position, etc.) were introduced to enhance the efficacy of selected OPNAs. Improved OPNAs exhibited a dose-dependent reduction in viral replication and nucleoprotein (NP) protein. When a mixture of oligoes was applied to infected cells, viral titer and NP levels decreased by more than eightfold.In this study, we have developed a modified PNA ASO platform with exceptional chemical stability, high binding affinity, and cellular permeability. These findings indicate that OPNAs are a promising platform for the development of antivirals to combat future pandemic viral infections that do not require a carrier.